PRODUCTION NUGGET Of WHITE OYSTER MUSHROOM WITH ADDITION OF SNAKEHEAD FISH - Mercia Yolanda Ashari; Usman Pato; Evy Rossi (Jurnal Sagu, 2022)
The purpose of this research was to obtain the best combination for making white oyster mushroom nuggets with the addition of snakehead fish. This study was conducted by using a completely randomized design with four treatments and four replications. The treatments consisted of TG1 (100% white oyster mushroom : 0% snakehead fish), TG2 (90% white oyster mushroom: 10% snakehead fish), TG3 (80% white oyster mushroom: 20% snakehead fish), TG4 (70% white oyster mushroom : 30% snakehead fish). Data obtained were analyzed by using analysis of variance and followed by Duncan’s New Multiple Range Test (DNMRT) at 5%. Result showed that the combination of white oyster mushroom and snakehead fish significantly affected moisture, ash, fat, protein, and fiber, and descriptive sensory assessment such as colour, flavour, aroma and elasticity of nuggets. The best treatment was TG4 (70% white oyster mushroom : 30% snakehead fish) with 54.91% moisture content, 1.71% ash, 12.62% fat, 35.24% protein, and 0.28% fiber. The overall sensory assessment of TG4 treatment was favored by panelists with a description of yellowish white color, a taste typical of snakehead fish, a little bit of typical smell of snakehead fish and white oyster mushroom and chewy texture.